First characterization of major histocompatibility complex class II DRB3 diversity in cattle breeds raised in Egypt - Hamada, Rania (2024)
Genes encoding bovine leukocyte antigen (BoLA) enable the immune system to identify pathogens. Therefore, these genes have been used as genetic markers for infectious and autoimmune diseases as well as for immunological traits in cattle. Although BoLA polymorphisms have been reported in various cattle breeds worldwide, they have not been studied in cattle populations in Egypt. In this study, we characterized BoLA-DRB3 in two local Egyptian populations and one foreign population using polymerase chain reaction-sequence-based typing (PCRSBT) method. Fifty-four previously reported BoLA-DRB3 alleles and eight new alleles (BoLA-DRB3*005:08, *015:07, *016:03, *017:04, *020:02:02, *021:03, *164:01, and *165:01) were identified. Alignment analysis of the eight new alleles revealed 90.7–98.9 %, and 83.1–97.8 % nucleotide and amino acid identities, respectively, with the BoLA-DRB3 cDNA clone NR-1. Interestingly, BoLA-DRB3 in Egyptian cattle showed a high degree of allelic diversity in native (na = 28, hE > 0.95), mixed (na = 61, hE > 0.96), and Holstein (na = 18, hE > 0.88) populations. BoLA-DRB3*002:01 (14.3 %), BoLA-DRB3*001:01 (8.5 %), and BoLA-DRB3*015:01 (20.2 %) were the most frequent alleles in native, mixed, and Holstein populations, respectively, indicating that the genetic profiles differed in each population. Based on the allele frequencies of BoLA-DRB3, genetic variation among Egyptian, Asian, African, and American breeds was examined using Nei’s distances and principal component analysis. The results suggested that native and mixed cattle populations were most closely associated with African breeds in terms of their gene pool, whereas Holstein cattle were more distinct from the other breeds and were closely related to Holstein cattle populations from other countries.